The effects of Sodium-glucose cotransporter 2 inhibitors on adipose tissue in patients with type 2 diabetes: A meta-analysis of randomized controlled trials - Liu, Xindong; Chen, Ying; Liu, Tao; Cai, Ling; Yang, Xiaofeng; Mou, Chuan (Frontiers in Endocrinology, 2023)
Purpose To systematically evaluate the effect of Sodium-glucose cotransporter 2 (SGLT2) inhibitors on adipose tissue in patients with type 2 diabetes. Methods We searched PubMed, Cochrane Library, EMBASE, and Web of science databases for literature pertaining to Randomized controlled trials (RCTs) of SGLT2 inhibitors in treating type 2 diabetes patients. The retrieval time was from the date of establishment of the databases to September 1, 2022. Meta-analysis was performed using RevMan5.4 software. Results Totally 551 patients were included in 10 articles. Meta-analysis results showed that compared with the control group, the visceral adipose tissue (WMD = -16.29 cm2, 95% CI: -25.07 -7.50, P<0.00001), subcutaneous adipose tissue (WMD = -19.34 cm2, 95% CI: -36.27 -2.41, P<0.00001), body weight (WMD = -2.36 kg, 95% CI: -2.89 -1.83, P<0.00001) and triglyceride (WMD = -24.41 mg/dl, 95% CI: -45.79 -3.03, P = 0.03) of the trial group significantly reduced. Conclusion SGLT2 inhibitors cause significant reductions in visceral adipose tissue, subcutaneous adipose tissue, body weight and triglycerides in type 2 diabetes patients, which may be attributed to the protective effect of the inhibitors on cardiovascular system.